IDENTIFICATION AND PREVALENCES PARASITE NEMATODE ON ETAWA CROSSBREED GOAT IN SUKAWATI SUBDISTRICT, GIANYAR REGENCY - Pangaribuan, Viany Ekklesia; Apsari, Ida Ayu Pasti; Sulabda, I Nyoman; Mufa, Romy Muhammad Dary (Buletin Veteriner Udayana, 2024)
Etawa crossbreed goat have farmed in Sukawati Subdistrict, Gianyar Regency. As a ruminant, goat had risked to get infected by nematode parasites in Sukawati Subdistrict, Gianyar Regency. This study had known to identification and prevalences parasite nematode cluster in Sukawati Subdistrict, Gianyar Regency. This study had bought some sample then have preserved with 10% formalin. The result is, prevalence of nematode parasite is 14% and nematode who can identification is Skrjabinema spp.; Strongyloides sp.; and Strongyl-type. Prevalence nematode in Sukawati Subdistrict more less than another place. From the results who have, cage cleanliness should be upgrade for minimalize nematode parasite infection.